Eros reinventado: uma leitura da poesia de Yêda Schmaltz - VIEIRA JÚNIOR, Paulo Antônio (2009)
This work is a research about the writer Yêda Schmaltz, this poetry that revives the Eros face through the mytological characters Penélepe, Dioniso, Áthis, Eco, Narciso and other myths. The initial propose is to study the complete works of the poetry especially books like A alquimia dos nós, Baco e as Anas brasileiras, A ti Áthis and Ecos: a jóia de Pandora, works that show better the Eros images, besides that she uses the Greek mytology. First of all we used works about mitology and platonic philosophy to understand how the God of love is showed on the Ocident. We used too a lot of poets that maked of love feeling as subject for his poems, like Safo, Petrarca, Camões and Álvares de Azevedo. Our objetive is seeing how Yêda Schmaltz is an heir of this poets. So we arrived at the conclusion that Yêda Schmaltz makes a modern poem when she revives Eros. According to Alfredo Bosi the subjective about the poems is giving the ways of the resistence of modern artists